A Study of Factor Affecting the Software Application Development in Indonesian Creative Industry - Chandra, Adhi Nugroho; Kurniawan, Yohannes (Bina Nusantara University, 2015)
The creative industries promising opportunities, especially the interactive game business. creative industries is still undeveloped, but lately has been showing its contribution to the economic development of Indonesia. Implementation of the Information and Communication Technology (ICT) strategy is a new discourse that can provide great opportunities for the entrepreneurial. This study aims to reveal the level of implementation of ICT strategies, the role of government influence on the development of business, industry conditions as well as the existing value chain in the interactive games industry. Type of research conducted by descriptive research, qualitative analysis was based on the findings of desk research / literature, interviewsources, and the researcher's own knowledge. Level of subjectivity can be minimized with the help of quantitative analysis and the selection of competent resource persons in the field interviews. Secondary dataobtained from the creative economy planning books in 2025, which was published by the Ministry of Commerce of the Republic of Indonesia. Based on the research results, it is concluded that the implementation of ICTstrategies by entrepreneurs in the interactive games industry is still less, and this is partly because in general the industry is still small-scale and micro enterprises, mash the industry is relatively new in the world of business,and entrepreneurs are still concentrating the creation, production, and distributio, commercialization are being developed. In general, interactive games industry is growing. In the future, need to research business model and business strategy, so it would complement the models developing strategy in the game interactive industry.